Narrative in Urban Planning A Practical Field Guide - Ameel, Lieven (Urban Studies, 2023)
What do planners need to know in order to use narrative approaches responsibly in their practice? This practical field guide makes insights from narrative research accessible to planners through a glossary of key concepts in the field of narrative in planning. What makes narratives coherent, probable, persuasive, even necessary - but also potentially harmful, manipulative and divisive? How can narratives help to build more sustainable, resilient, and inclusive communities? The authors are literary scholars who have extensive experience in planning practice, training planning scholars and practitioners or advising municipalities on how to harness the power of stories in urban development.